2013
DOI: 10.1111/jsr.12064
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in objective measures of sleep in post‐traumatic stress disorder and healthy control subjects

Abstract: Summary A growing literature shows prominent sex effects for risk for PTSD and associated medical comorbid burden. Prior research indicates that PTSD is associated with reduced slow wave sleep (SWS), which may have implications for overall health, and abnormalities in REM sleep, which have been implicated in specific PTSD symptoms, but most research has been conducted in male subjects. We therefore sought to compare objective measures of sleep in male and female PTSD subjects with age and sex-matched control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 30 publications
2
55
1
Order By: Relevance
“…Inclusion criteria for both groups was 20–50 years of age and body mass index (BMI) <30 kg/m 2 (O’Donovan et al, 2011; Richards et al, 2013). Exclusion criteria included: history of traumatic brain injury; presence of neurologic disorders or systemic illness; sleep apnea; pregnancy; alcohol abuse in the previous 2 years, substance abuse in the previous 1 year; any history of psychiatric disorder with psychotic features, bipolar disorder or compulsive disorders; and use of any psychiatric, anticonvulsant, antihypertensive, steroidal, lipid-lowering, or any other prescription medications or estrogen replacement therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria for both groups was 20–50 years of age and body mass index (BMI) <30 kg/m 2 (O’Donovan et al, 2011; Richards et al, 2013). Exclusion criteria included: history of traumatic brain injury; presence of neurologic disorders or systemic illness; sleep apnea; pregnancy; alcohol abuse in the previous 2 years, substance abuse in the previous 1 year; any history of psychiatric disorder with psychotic features, bipolar disorder or compulsive disorders; and use of any psychiatric, anticonvulsant, antihypertensive, steroidal, lipid-lowering, or any other prescription medications or estrogen replacement therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The recording montage consisted of C3/A2, C4/A1, O1/A2 and O2/A1 electroencephalograms, bilateral electroculograms, a bipolar submental electromyogram, bilateral anterior tibialis electromyograms and electrocardiograms (Richards et al, 2013; Rechtschaffen and Kales, 1968). Electrode impedance was set at <5000 ohms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gender differences in the relationship between PTSD and sleep have now begun to be reported (Kobayashi, Cowdin, & Mellman, 2012; Kobayashi & Mellman, 2012; Richards et al, 2013). For example, observed sex differences in the sleep symptoms of PTSD may vary with hormonal levels and phase of the menstrual cycle in women (Kobayashi et al, 2012).…”
Section: Related Clinical Findingsmentioning
confidence: 99%
“…Woodward et al (2000) found that the non-REM-sleep sigma-band spectral power exhibited a strong positive correlation with the hyperarousal symptoms cluster. The non-REM delta energy did not exhibit a significant correlation with the overall PTSS severity or symptoms clusters (Richards et al, 2013).…”
Section: Eeg Spectral Analysis Studiesmentioning
confidence: 98%